Quantificação de ferro no cérebro humano através de ressonância magnética - Holz, Tiago Garcia (2020)
Introduction: The chemical element iron is critical to the normal development, function and chemical balance of cells, especially in central nervous system. Because cells have various mechanisms of control of iron homeostasis, and yet, it´s deposit in mammal’s brain is normal during ageing. This accumulation can contribute to the generation of free radicals and thus unbalance the function of central nervous system cells, causing neurodegeneration. This process can be accelerated under some pathological conditions, promoting faster neurodegeneration. An in vivo brain iron quantification, which can be performed by magnetic resonance imaging, becomes operative since iron brain deposits is part of the normal brain ageing and, when excessive, may be determinant for the development of degenerative diseases. Purpose: to quantify the iron deposits in the basal ganglia and evaluate its relationship with age, sex, body mass index and brain laterality. Methods: Prospective observational study. Data from age, sex and nutritional status were collected from the patients' electronic medical records. The concentration of iron deposits in the brain was assessed using 3.0 Tesla whole brain magnetic resonance imaging. The regions of interest were measured by two experienced radiologists. Results: Of the 138 participants, 96 (69.6 %) were female, and the mean age was 47 ± 19 years. The Kappa coefficient of interobserver agreement was very strong (k = 0.92, p<0.001). Age showed a moderate correlation between iron deposits in the caudate and putamen nuclei, on both the right and left sides (p<0.001). In relation to overall and right-handed individuals, a significantly higher iron concentration was observed on the left side when compared to the right side for the caudate nucleus, putamen, thalamus, globus pallidus, and centrum semiovale (p<0.001). As for left-handed individuals, a significantly higher iron concentration also was observed in the left side when compared to the right side for the putamen (p = 0.026) and centrum semiovale (p = 0.028). A weak correlation was shown between body mass index and left and right substantia nigra (respectively, r = 0.196; p = 0.022 and r = 0.211; p = 0.013), left caudate nuclei (r = 0.224; p = 0.008), left putamen (r = 0.199; p = 0.020) and right globus pallidus (r = 0.186; p = 0.029). Conclusion: our results showed a significantly higher iron deposit on the left side in most brain regions. It also demonstrated that the concentration of iron in healthy individuals appears to be a natural process that occurs with advancing age. In addition, the body mass index may also be related to iron overload, especially in the caudate nucleus.